In Vitro and In Vivo Quality Evaluation of Glibenclamide Tablets Marketed in Addis Ababa, Ethiopia. (18th July 2018) - Kassahun, Haile; Asres, Kaleab; Ashenef, Ayenew
Abstract : Good quality drugs fulfilling the regulatory parameters and produced per the current good manufacturing (CGMP) standards are very critical for best therapeutic outcome in patient therapy. Hence, this study assesses quality as well as physicochemical bioequivalence of five brands of glibenclamide tablets marketed in Addis Ababa using in vitro and in vivo methods. Friability, disintegration, dissolution, and assay for the content of active ingredients were evaluated using the methods described in the British Pharmacopeia (2009) and United States Pharmacopeia (2007). All the brands of glibenclamide tablets complied with the official specification for hardness, friability, disintegration, and assay. Difference factor (f1) values were less than 15 and similarity factor (f2) values were greater than 50 for all products of glibenclamide. The hypoglycemic effect of different products of glibenclamide tablets was evaluated on normoglycemic mice. The in vivo studies indicated that there is no significant difference in percent reduction of blood glucose level between the brands of glibenclamide and the innovator product (p > 0.05). Hence, based on the in vivo results and in vitro dissolution studies, the brands might be substituted with the innovator product in clinical practice.